Dense water formation in the north‐western Mediterranean area during HyMeX‐SOP2 in 1/36° ocean simulations: Sensitivity to initial conditions. Issue 8 (6th August 2016) - Léger, Fabien; Lebeaupin Brossier, Cindy; Giordani, Hervé; Arsouze, Thomas; Beuvier, Jonathan; Bouin, Marie‐Noëlle; Bresson, Émilie; Ducrocq, Véronique; Fourrié, Nadia; Nuret, Mathieu
Abstract: The north‐western Mediterranean Sea is a key location where intense air‐sea exchanges occur in autumn and winter. The succession of strong mistral and tramontane situations, leading to significant evaporation and ocean heat loss, is well known as the controlling factor in the dense water formation (DWF) with deep convection episodes. During HyMeX‐SOP2 (1 February to 15 March 2013), several platforms sampled the area in order to document DWF and air‐sea exchanges. This study investigates the ability of the NEMO‐WMED36 ocean model (1/36°‐resolution), driven in surface by the hourly air‐sea fluxes from the AROME‐WMED forecasts (2.5 km resolution), to represent DWF during HyMeX‐SOP2 and focuses on the sensitivity to initial conditions. After a short evaluation of the atmospheric forcing, the high‐resolution oceanic simulations using three different data sets as initial and boundary conditions are compared to observations collected during the field campaign. It evidences that using regional model outputs may lead to unrealistic thermohaline characteristics for the intermediate and deep waters, which degrade the simulated new dense water formed. Using ocean analyses built from observations, permits to obtain more realistic characteristics of the Western Mediterranean dense water. However, a low stratification favors an overestimation of the convective area and of the DWF rate. The DWF chronology is also impacted. Nevertheless, in every run, SOP2 is characterized by the production of water denser than 29.11 kg m −3 with a peak during the strong mistral event of 23–25 February followed by a period of restratification, before a last event of bottom convection on 13–15 March. Key Points: Three high‐resolution ocean simulations are compared to HyMeX SOP2 observations The NEMO‐WMED36 model is able to reproduce dense water formation during winter 2013. The large sensitivity of dense water formation to initial conditions is highlighted